Mineral dialyzability in milk and fermented dairy products fortified with FeNaEDTA - Drago, Silvina Rosa (2008)
Iron, zinc, and calcium dialyzability and ascorbic acid (AA) concentrations were evaluated in milk and yogurt fortified with FeNaEDTA (FE) or ferrous sulfate (FS) as a control, with or without AA addition. The values obtained for FE iron dialyzability in milk were much higher than those obtained for FS. The addition of AA to milk improved Fe dialyzability when using FS and slightly decreased Fe dialyzability in the FE-fortified nonfermented samples. Milk fermentation increased iron availability from both iron sources. Zinc and calcium dialyzability in products containing any of the two iron sources was increased in fermented milks. EDTA improved Zn dialyzability from intrinsic zinc in every manufactured dairy product. Whereas for milks fortified with FS and stored at 4°C for 24 h, the AA content remained close to the original concentration, a higher AA degradation was observed when milks were fortified with FE.